Click to Chat

1800-2000-838

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```
(sinx)3-(cosx)3=[(sinx)2-(cosx)2][1-2*(sinx)2*(cosx)2]
here (sinx)3 means cube of sinx and similarly other powers .
```
6 years ago

510 Points
```										(sinx)3 -(cosx)3 = (sinx-cosx)(sin2 x +cos2 x -sinxcosx) or     (sinx+cosx)(1-sin2x/2)
sin2 x -cos2 x =(sinx-cosx)(sinx+cosx)
on putting these
we get
(sinx+cosx)(1-sin2x/2 ) = ((sinx+cosx)(sinx-cosx)(1-2(sinxcosx)2 )         or
(sinx+cosx) {1-sin2x/2 - (sinx-cosx)(1-2(sinxcosx)2 } = 0
sinx +cosx =0                            or                  {1-sin2x/2 -(sinx-cosx)(1-2(sinxcosx)2 }=0
tanx=-1                                    or            {1-sin2x/2  -(sinx-cosx)(1-(sin2x)2 /2 ) =0
x =npi -pi/4                               or           (sinx-cosx)2 =1-sin2x ,so nw sustitute the value of sin2x in above eq
& simplify it...

```
6 years ago
Think You Can Provide A Better Answer ?

Other Related Questions on Trigonometry

View all Questions »
• Complete JEE Main/Advanced Course and Test Series
• OFFERED PRICE: Rs. 15,900
• View Details